Reproductive History of a Woman With 8p and 18p Genetic Imbalance and Minor Phenotypic Abnormalities - Pendina, Anna A.; Shilenkova, Yulia V.; Talantova, Olga E.; Efimova, Olga A.; Chiryaeva, Olga G.; Malysheva, Olga V.; Dudkina, Vera S.; Petrova, Lubov' I.; Serebryakova, Elena A.; Shabanova, Elena S.; Mekina, Irina D.; Komarova, Evgeniia M.; et al. (Frontiers in Genetics, 2019)
We report on the phenotype and the reproductive history of an adult female patient with an unbalanced karyotype: 8p23 and 18p11.3 terminal deletions and 8p22 duplication. The indication for karyotyping of the 28-year-old patient was a structural rearrangement in her miscarriage specimen: 45,ХХ,der(8;18)t(8;18)(p23;p11.3). Unexpectedly, the patient had the same karyotype with only one normal chromosome 8, one normal chromosome 18 and a derivative chromosome, which was a product of chromosomes 8 and 18 fusion with loss of their short arm terminal regions. Fluorescence in situ hybridization revealed that derivative chromosome was a pseudodicentric with an active centromere of chromosome 8. Array comparative genomic hybridization confirmed 8p and 18p terminal deletions and additionally revealed 8p22 duplication with a total of 43 OMIM annotated genes being affected by the rearrangement. The patient had minor facial and cranial dysmorphia and no pronounced physical or mental abnormalities. She was socially normal, had higher education and had been married since the age of 26 years. Considering genetic counseling, the patient had decided to conceive the next pregnancy through in vitro fertilization (IVF) with preimplantation genetic testing for structural chromosomal aberrations (PGT-SR). She underwent four IVF/PGT-SR cycles with a total of 25 oocytes obtained and a total of 10 embryos analyzed. Only one embryo was balanced regarding chromosomes 8 and 18, while the others were unbalanced and demonstrated different combinations of the normal chromosomes 8 and 18 and the derivative chromosome. The balanced embryo was transferred, but the pregnancy was not registered. After four unsuccessful IVF/PGT-SR cycles, the patient conceived naturally. Non-invasive prenatal testing showed additional chromosome 18. The prenatal cytogenetic analysis of chorionic villi revealed an abnormal karyotype: 46,ХХ,der(8;18)t(8;18)(p23;p11.3)mat,+18. The pregnancy was terminated for medical reasons. The patient has a strong intention to conceive a karyotypically normal fetus. However, genetic counseling regarding this issue is highly challenging. Taking into account a very low chance of balanced gametes, emotional stress caused by numerous unsuccessful attempts to conceive a balanced embryo and increasing age of the patient, an IVF cycle with a donor oocyte should probably be considered.